2015
DOI: 10.17722/ijme.v6i1.218
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of key Macroeconomic factors on Economic Growth of Bangladesh: a VAR Co-integration Analysis

Abstract: Abstract-This study analyzes the impact of key macroeconomic factors on economic growth of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 14 publications
(14 reference statements)
0
3
0
Order By: Relevance
“…Hence, this study relies on both the endogenous and exogenous growth theories. Different studies such as (Kryeziu, 2016;Ali et al, 2015;Antwi et al, 2013;Iqbal and Zahid, 1998;Suliman and Osman, 1994;Grossman and Helpman, 1994) have shown that economic growth relates to macroeconomic variables. Although economic growth is, a complex macroeconomic phenomenon given the fact that it is still difficult to distinguish which of the determinant that has greater or less impact on growth (Kryeziu, 2016).…”
Section: Economic Growth Theoriesmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, this study relies on both the endogenous and exogenous growth theories. Different studies such as (Kryeziu, 2016;Ali et al, 2015;Antwi et al, 2013;Iqbal and Zahid, 1998;Suliman and Osman, 1994;Grossman and Helpman, 1994) have shown that economic growth relates to macroeconomic variables. Although economic growth is, a complex macroeconomic phenomenon given the fact that it is still difficult to distinguish which of the determinant that has greater or less impact on growth (Kryeziu, 2016).…”
Section: Economic Growth Theoriesmentioning
confidence: 99%
“…In Pakistan, high inflation rate, increasing foreign debt, low level of physical and human capital is mainly the source of unstable economic growth inherent in the economy. More so, macroeconomic stability in any nation leads to economic growth as every nation aspires for a sustainable economic growth, which measures the entire economic development of a country and brings about good standard of living in an economy (Ali et al, 2015;Suliman and Osman, 1994).…”
Section: Economic Growth Theoriesmentioning
confidence: 99%
“…The prime objective of this research is to determine the effect of macro-economic factors on the economic growth of Bangladesh. Literature review indicates that local and international researchers, together with Akram et al (2011), Enu et al (2013), Biswas and Saha (2014), Ismaila and Imoughele (2015), Ali et al (2015), Wadud (2017), Kotesware and Sera (2017), Simionescu et al (2017), Anik and Biplob (2019), Haque (2020), Oyebowale and Algarhi (2020), Ghimire et al, (2020), Jannat et al (2020), Jacob et al (2021), Mukit (2021), Hassan et al (2022), Ajmair and Tahir, (2022) and many other studies carried out extensive study to express the effect of macroeconomic indicators on various economies. Although all of the abovementioned research scholars use GDP as a substitute for economic growth, their independent variables and research findings vary greatly from economy to economy and researcher to researcher.…”
Section: Introductionmentioning
confidence: 99%
“…Although all of the abovementioned research scholars use GDP as a substitute for economic growth, their independent variables and research findings vary greatly from economy to economy and researcher to researcher. Among various macroeconomic indicators, inflation shows a positive relationship (Enu et al, 2013;Ali et al, 2015, Jacob et al, 2021Haque, 2020;Mukit, 2021) negative relationship (Akram et al, 2011;Biswas & Saha, 2014;Tien, 2021, Hassan et al, 2022Ajmair & Tahir, 2022) and insignificant relationship (Ghimire et al, 2020, Wadud, 2017Adu-Gyamfi et al, 2020) with economic growth. Moreover, export has a positive relationship (Biswas & Saha, 2014;Hassan et al, 2022;Oyebowale & Algarhi, 2020) as well as a negative relationship (Jannat et al, 2020) and an insignificant relationship (Wadud, 2017;Haque, 2020;Mukit, 2021) with economic growth.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Roespinoedji, et al, (2019); Nkoro and Uko (2016); Magoti and Mtui, (2020) employed the use of ARDL in analysing the secondary data inherent in their studies. Taghizadeh- Hesary and Yoshino (2015); Akpan and Atan, (2015) used the SVAR, while Farzanegan (2011) and Ali et al, (2015) used VAR in carrying out their analyses, with secondary data in the oil related studies. To the best of my knowledge, there is no other oil related study either for oil-importing, oil-exporting, developed or for developing nations and even for emerging economies carried out survey data analysis.…”
mentioning
confidence: 99%